Optical properties of nanoparticles thin film in organic light emitting diode (OLED) / Siti Munirah Che Noh - Siti Munirah , Che Noh (2017)
In-depth study on silver nanoparticles (Ag) has been conducted through UV-Visible (UV-Vis) spectroscopy, atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), and current-brightness-voltage (IVL) measurement. A thin layer of silver nanoparticles was produced by depositing silver thin film on top of indium tin oxide (ITO) substrate via electron beam (e-beam) deposition system. Nanoparticles formed through self-assemble dewetting process after annealing treatment in furnace with temperature ranging from 200 oC to 400 oC, which yields different sizes of nanoparticles. The obtained results were used as training and checking data input for soft computing methodology Support Vector Regression (SVR). The SVR was used for estimation of sizes of nanoparticles formed on top of substrate at certain temperatures. The experimental results show an improvement in predictive accuracy and capability of generalization which can be achieved by the SVR_poly approach in compare to SVR_rbf and SVR_lin methodology. Estimation of local surface plasmon resonance (LSPR) over a broad wavelength range is simulated using an adaptive neurofuzzy inference system (ANFIS) method. The ANFIS methodology allows for estimation of sizes of granular structures formed on top of a substrate at certain temperatures, whereupon these intelligent estimators are implemented using MATLAB and their subsequent performances are investigated. The results presented in this thesis work show the effectiveness of the method of simulation. The plasmonic effect of Ag NPs with remarkable optical properties lead us to integrate the particles in the red and green phosphorescent organic light emitting diodes (OLED) as hole injection layer (HTL). The device with Ag NPs layer achieved more than 3 folds enhancement compared to the device without Ag NPs.